Drilling into community perceptions of coal seam gas in Roma, Australia. Issue 3 (July 2016) - Bec, Alexandra; Moyle, Brent D.; McLennan, Char-lee J.
Highlights: Social exchange theory and social representation theory have been used as a lens to understand community perceptions of mining induced change. There is a lack of information communicated to community members about the impacts of coal seam gas extraction. Critical facilities and services have been strained as a result of mining growth and expansion. Mining activity is hindering other economic sectors, particularly agriculture. Abstract: Coal seam gas (CSG) extraction and its conversion into liquefied natural gas (LNG) for overseas export is a recent phenomenon in Australia. These activities have, not surprisingly, attracted significant attention because of their perceived impacts on the environment and communities. However, community and stakeholder perceptions of these impacts, particularly for local development, have gone virtually unexamined in the literature. This paper aims to bridge this gap by exploring local perceptions of CSG extraction in a rural Australian community. In doing so, the research determines the efficacy of using social representation theory (SRT) and social exchange theory (SET) to assess community perceptions of mining-induced change. Findings reveal that the community perceives CSG extraction to provide positive economic impacts but is concerned about its ability to facilitate long-term economic growth and development. Long-term residents considered regional development to be targeted towards satisfying the needs of mining companies and 'new' migrants to the region. A lack of information about the impacts of CSG extraction has led to heightened apprehension among long-term residents.